Optimization of environmental factors affecting initial growth of Norway spruce seedlings - Johansson, Karin; Langvall, Ola; Bergh, Johan (Silva Fennica, 2012)
The purpose of the study was to create a near optimal environment for seedling establishment and growth, without the restrain of water and nutrients but under climate conditions typical for the region. This to give us valuable knowledge about the growth potential of different seedling types in the field. The experimental site was situated in southern Sweden. Six treatment combinations were applied including two site treatments; 1) soil inversion, i.e. the control treatment, and 2) soil inversion, drip irrigation and fertilization combined with plastic cover mulch, i.e. the optimization treatment, and three seedling types of Norway spruce (Picea abies L. Karst.), (a) a 2-year-old Plug+1 seedling, (b) a 1.5-year-old containerized seedling and (c) a 10-week-old mini seedling. Effects on seedling nutrient status and growth were studied during the first three years after planting. Height, diameter and biomass of the seedlings grown in the optimized environment were significantly greater than for seedlings grown in the control. The Plug+1 seedlings grown in the optimization treatment had, after three years, reached a height of 124 cm, while the containerized seedlings were 104 cm and the mini seedlings 45 cm. In practical plantations, this height is usually gained after 5â10 years depending on planting conditions. Biomass partitioning did not differ between optimization treatments, but between seedling types. The mini seedlings allocated less biomass to the roots and more biomass to needles and stem in comparison with the two other seedling types. Mini seedlings also broke bud earlier. Throughout the experimental period, seedling nutrient status for all treatment combinations was followed and a balanced nutrient supply of macro- and micronutrients was given in the optimization treatment. Nutrient concentrations were constantly higher in seedlings grown in the optimization treatment, but the difference decreased over time. Results from this study shows that, by improving site conditions associated with fast establishment, growth check can be avoided.